2021
DOI: 10.3389/fcvm.2021.574360
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Thromboembolic Pulmonary Hypertension – What Have We Learned From Large Animal Models

Abstract: Chronic thrombo-embolic pulmonary hypertension (CTEPH) develops in a subset of patients after acute pulmonary embolism. In CTEPH, pulmonary vascular resistance, which is initially elevated due to the obstructions in the larger pulmonary arteries, is further increased by pulmonary microvascular remodeling. The increased afterload of the right ventricle (RV) leads to RV dilation and hypertrophy. This RV remodeling predisposes to arrhythmogenesis and RV failure. Yet, mechanisms involved in pulmonary microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 140 publications
(217 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, Stephenson et al reported the feasibility of the usage of Holstein calves in developing a robotically assisted microsurgical system to perform coronary artery anastomoses [20]. In another review, studies on the pathophysiology Large Animal Models in Cardiovascular Research DOI: http://dx.doi.org/10.5772/intechopen.105754 of chronic thromboembolic pulmonary hypertension using large animal models such as dogs and pigs using either indwelling or Swan Ganz catheters are summarized [21]. An important translational feature of pig models is the possibility of percutaneous coronary intervention using human clinical equipment, and the procedures using metallic stents or angioplasty balloons [22,23].…”
Section: Advantages Of Large Animal Models For Cardiovascular Researc...mentioning
confidence: 99%
“…On the other hand, Stephenson et al reported the feasibility of the usage of Holstein calves in developing a robotically assisted microsurgical system to perform coronary artery anastomoses [20]. In another review, studies on the pathophysiology Large Animal Models in Cardiovascular Research DOI: http://dx.doi.org/10.5772/intechopen.105754 of chronic thromboembolic pulmonary hypertension using large animal models such as dogs and pigs using either indwelling or Swan Ganz catheters are summarized [21]. An important translational feature of pig models is the possibility of percutaneous coronary intervention using human clinical equipment, and the procedures using metallic stents or angioplasty balloons [22,23].…”
Section: Advantages Of Large Animal Models For Cardiovascular Researc...mentioning
confidence: 99%
“…However, there are few studies exploring the aforementioned pathological and physiological mechanisms of CTEPD, mainly due to the difficulty in establishing animal models for CTEPD. Previous attempts by researchers to establish animal models through repeated thrombus embolization have been unsuccessful [6,7], primarily due to the strong fibrinolytic capacity of animals, which leads to rapid dissolution of injected thrombi, preventing chronic remodeling. Some researchers have ligated the left pulmonary artery in piglets and repeatedly injected non-dissolvable microspheres through the external jugular vein to induce right pulmonary embolism and establish a CTEPD model.…”
Section: Introductionmentioning
confidence: 99%
“…Large animal models of CTEPH have advanced our understanding of the pathophysiology of CTEPH (Mulchrone et al 2019;Stam et al 2021), but typically do not report local mechanical stimuli for disease progression such as WSS. Image-based computational uid dynamics (CFD) modeling can compute pulmonary artery blood ow with high spatial resolution (Burrowes et al 2017;Bordones et al 2018; Wang et al 2020), from which WSS can be calculated.…”
Section: Introductionmentioning
confidence: 99%